Risk factors for catastrophic health spending in Peru today in Peru today - Quiroz Vera, Eduardo Fernando (2018)
The present investigation makes an approximation to the expenditures in health and catastrophic expenditure, constructing six models of catastrophic calculation, where the variants are the types of food expenditure described by the national survey of households ENAHO 2017. In all the models the variables age and sex of the head of household were not significant. On the other hand, it was found that the presence of children under 5 years of age, the presence of people over 65 years of age and having chronic diseases have a significant and positive influence on catastrophic spending. Finally, the probability of incurring a catastrophic expense is when you have families with expenses higher than 20% of their available expenses.